Peripheral Reading on Nicasio Álvarez de Cienfuegos’s Poetry - Miguel Ángel LAMA (Cuadernos Dieciochistas)
This study tries to complete from different sides some aspects already dealt with by the critics about the poetry of Nicasio Álvarez de Cienfuegos. Such as the formation of its limited corpus, its verse lines not collected among his works and which were published in Gonzalo de Córdoba, López Peñalver’s version of the French novel or the powerful feeling of death which can be noticed in his most spirited and famous compositions.